Pengelolaan Sarana dan Prasarana dalam Meningkatkan Kualitas Pembelajaran: Studi Deskriptif di SDN Percontohan Kecamatan Badar Kabupaten Aceh Tenggara - Edi Noviar; Abdurrahman Abdurrahman; Alfi Syahrin (Journal on Education, 2025)
This research aims to analyze the management of facilities and infrastructure at SDN Perpilotan, Badar District, Southeast Aceh Regency and its impact on the quality of learning. The method used is descriptive qualitative research, with data collection through interviews and observation. The research results show that good management of Facilities and Infrastructure makes a positive contribution to the teaching and learning process, even though there are obstacles such as incompatibility of goods received and teachers' limited time for maintenance. The conclusion of this research emphasizes the importance of systematic planning and evaluation in the management of facilities and infrastructure to improve the quality of education